2010
DOI: 10.1021/es902838n
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Life Cycle Comparison of Algae to Other Bioenergy Feedstocks

Abstract: Algae are an attractive source of biomass energy since they do not compete with food crops and have higher energy yields per area than terrestrial crops. In spite of these advantages, algae cultivation has not yet been compared with conventional crops from a life cycle perspective. In this work, the impacts associated with algae production were determined using a stochastic life cycle model and compared with switchgrass, canola, and corn farming. The results indicate that these conventional crops have lower en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
630
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 964 publications
(643 citation statements)
references
References 40 publications
8
630
0
5
Order By: Relevance
“…Most nutrients consumed during growth are in the LEA and a portion of them is recovered during biogas production. Previous work showed that electricity production and nutrient recycling greatly affect energy and nutrient demands in the process (Campbell et al 2009;Clarens et al 2010Clarens et al , 2011Frank et al 2011aFrank et al , 2012Lardon et al 2009;Stephenson et al 2010).…”
Section: Context and Motivationmentioning
confidence: 99%
“…Most nutrients consumed during growth are in the LEA and a portion of them is recovered during biogas production. Previous work showed that electricity production and nutrient recycling greatly affect energy and nutrient demands in the process (Campbell et al 2009;Clarens et al 2010Clarens et al , 2011Frank et al 2011aFrank et al , 2012Lardon et al 2009;Stephenson et al 2010).…”
Section: Context and Motivationmentioning
confidence: 99%
“…11,[13][14][15][16][17][18] In this study, we aimed to further assess the capability of these four green microalgae species in the simultaneous removal of various contaminants (nitrogen, phosphorus, metals, organic compounds) in real wastewater. Estrogenic EDCs such as nonylphenol possess the ability to disrupt the endocrine systems of higher organisms by interacting with the estrogen receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, prospective largescale microalgae production locations are often arid areas that exhibit high evaporative losses of between 20-40ML ha -1 annually, which limits the scope and scale of microalgae production in many regions (Chisti 2007;McHenry 2010). Nevertheless, microalgae appear to exhibit superior overall environmental credentials to terrestrial biofuels with smaller land use and water consumption per unit of output compared to agricultural crops (Sheehan et al 1998;Huntley and Redalje 2006;Chisti 2007;Gross 2007;Hankamer et al 2007;Cantrell et al 2008;Chisti 2008;Dinh et al 2009;Borowitzka and Moheimani 2010;Clarens et al 2010). This ability is essentially a factor of their potential to achieve a higher real photosynthetic efficiency than typical terrestrial crops (Sheehan et al 1998;Vasudevan and Briggs 2008;Amin 2009).…”
Section: How Thermal MD and Solution Mining Integrate With Microalgalmentioning
confidence: 99%
“…Whilst such diverse production options adds potential flexibility and diversity, it also necessitates robust culture pre-and-post-treatment and precise system control to avoid the many potential production problems (Schneider 2006;Wang et al 2008). As an example, if not managed effectively, industrial pond microalgae culture may create effluent waste water issues and become an unprofitable and energy intensive process (Wyman and Goodman 1993;Xiong et al 2008;Charcosset 2009;Borowitzka and Moheimani 2010;Clarens et al 2010). …”
Section: How Thermal MD and Solution Mining Integrate With Microalgalmentioning
confidence: 99%